Synthesis, solubility, plasma stability, and pharmacological evaluation of novel sulfonylhydrazones designed as anti-diabetic agents - Zapata-Sudo G; da Costa Nunes IK; Araujo JSC; da Silva JS; Trachez MM; da Silva TF; da Costa FP; Sudo RT; Barreiro EJ; Lima LM (Dove Medical Press, 2016)
Gisele Zapata-Sudo,1,2 Isabelle Karine da Costa Nunes,2 Josenildo Segundo Chaves Araujo,1,2 Jaqueline Soares da Silva,2 Margarete Manhães Trachez,2,3 Tiago Fernandes da Silva,1 Filipe P da Costa,2 Roberto Takashi Sudo,1,2 Eliezer J Barreiro,1,2 Lídia Moreira Lima1,2 1National Institute of Science and Technology on Drugs and Medicines, Federal University of Rio de Janeiro, Laboratory of Evaluation and Synthesis of Bioactive Compounds, Center of Health Sciences, Rio de Janeiro, Brazil; 2Program of Research in Drug Development, Institute of Biomedical Sciences, Federal University of Rio de Janeiro, Rio de Janeiro, Brazil; 3Department of Anesthesiology, Fluminense Federal University, Rio de Janeiro, Brazil Abstract: Neuropathy is a serious complication of diabetes that has a significant socioeconomic impact, since it frequently demands high levels of health care consumption and compromises labor productivity. Recently, LASSBio-1471 (3) was demonstrated to improve oral glucose tolerance, reduce blood glucose levels, and display an anti-neuropathy effect in a murine streptozotocin-induced diabetes model. In the present work, we describe the design, synthesis, solubility, plasma stability, and pharmacological evaluation of novel sulfonylhydrazone derivatives (referred to herein as compounds 4–9), which were designed by molecular modification based on the structure of the prototype LASSBio-1471 (3). Among the compounds tested, better plasma stability was observed with 4, 5, and 9 in comparison to compounds 6, 7, and 8. LASSBio-1773 (7), promoted not only hypoglycemic activity but also the reduction of thermal hyperalgesia and mechanical allodynia in a murine model of streptozotocin-induced diabetic neuropathic pain. Keywords: diabetes, sulfonylhydrazone, hypoglycemic activity, druglikeness, plasma stability, metabolite